Orhan Pamuk’s Melancholic Narrative and Fragmented Photographic Framing – Istanbul: Memories of a City (2005) - Koureas, Gabriel (My University, 2012)
This chapter aims to investigate the 'new symbols' that Pamuk uncovered in his pursuit of the melancholic soul of the city and the ways in which the symbols work for the clash and interlacing of cultures in order to reveal the precariousness of cultural realignments. It discusses the use of photography in Pamuk's book and the ways in which one can become intoxicated with memories through the juxtaposition of text and image. The chapter entitled 'Black and White' moves from the interior to the exterior in order to provide the same analogy in the relationship between photography and memory to the city where the interior of the 'bleak museum' and its melancholy is transferred to the cityscape of Istanbul and its psyche. In other words, the photographs provided the Freudian screen memories of the huzun, Pamuk wanted to describe and the embodiment of that loss he felt as he was growing up in Istanbul.
Keywords: Pamuk; Juxtaposition